Preparation method of high-dispersion sodium ion battery tin-hard carbon composite negative electrode material

By performing dopamine hydrochloride polymerization and sodium hydroxide treatment on the hard carbon surface in sodium ion batteries, combined with sodium borohydride reaction, high dispersion and uniform distribution of tin-hard carbon composite materials are achieved, and the performance of the negative electrode material of sodium ion batteries is solved. The problem of improving the cycle stability and charge and discharge capacity of the battery.

CN119297210AActive Publication Date: 2025-01-10SHENZHEN JANAENERGY TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411637926.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-10
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The performance of existing sodium ion battery negative electrode materials is insufficient, especially hard carbon materials have defects in cycle stability and charging and discharging platforms. It is difficult for traditional composite technology to achieve uniform distribution of tin particles in hard carbon substrates, resulting in a degradation of battery performance.

Method used

By performing in-situ polymerization and adsorption properties modification of dopamine hydrochloride on the hard carbon surface, combining sodium hydroxide solution and sodium borohydride hydrogen evolution inhibitory solution, uniform deposition and distribution of tin is achieved, forming a highly dispersed tin-hard carbon composite material .

Benefits of technology

The high specific capacity, good electrochemical performance and cycle stability of the tin-hard carbon composite material are achieved, and the hydrogen generation and equipment corrosion problems in traditional methods are avoided, and production safety and sustainability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297210A_ABST
    Figure CN119297210A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-dispersion sodium ion battery tin-hard carbon composite negative electrode material, which comprises the following steps: S1, pretreatment of a hard carbon material: taking porous hard carbon as a raw material, adding a dopamine hydrochloride solution for pretreatment, and filtering to obtain pretreated hard carbon; s2, hard carbon surface in-situ polymerization: adding the pretreated hard carbon into a sodium hydroxide solution, and filtering to obtain hydrophilic hard carbon; s3, preparation of composite particles: adding the hydrophilic hard carbon into a SnCl2 or SnCl4 solution for sanding and spray drying to obtain SnCl2-hard carbon or SnCl4-hard carbon composite particles; and S4, deposition of the tin-hard carbon composite material: adding the composite particles into a sodium borohydride hydrogen evolution reaction inhibition solution under an ice-water bath condition to obtain a Sn-hard carbon composite turbid liquid, and filtering to obtain the tin-hard carbon composite material. The method has the characteristics of uniform deposition and dispersion, good particle size and morphology adjustability and strong process controllability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery. Background Art

[0002] Lithium-ion batteries have always been the main choice in the field of energy storage due to their high energy density and relatively good cycle stability. However, the limited and uneven distribution of lithium resources restricts the large-scale application and cost of lithium-ion batteries. Sodium-ion batteries have gradually come into people's view due to their similar physical and chemical properties to lithium-ion batteries. Sodium is abundant in the earth's crust, widely distributed, and low in cost, which gives sodium-ion batteries a significant advantage in resource sustainability.

[0003] Although sodium-ion batteries have great potential in theory, they still face many challenges in practical applications. At present, the research on positive electrode materials for sodium-ion batteries has made significant progress, and a variety of materials with good electrochemical properties have been developed. However, the research on negative electrode materials for sodium-ion batteries is relatively lagging behind. The performance of negative electrode materials directly affects the capacity, cycle stability and charging efficiency of the battery. The ideal negative electrode material should have a low charge and discharge platform, high specific capacity and good cycle stability. At present, although hard carbon has been commercialized, there are still some problems, such as low capacity (generally less than 350 mAh / g), low initial coulombic efficiency, and poor rate performance.

[0004] Alloy negative electrodes have a high theoretical specific capacity. Among them, tin has a high comprehensive advantage due to its low operating voltage and high specific capacity (847 mAh / g), but its excessive volume expansion and poor material cyclability hinder the in-depth research of tin negative electrodes.

[0005] The combination of hard carbon materials and high-capacity tin negative electrode materials can combine the advantages of hard carbon and tin, in which the carbon material acts as a buffer substrate, which can prevent particle aggregation, reduce volume expansion, and build a conductive network, thereby significantly improving the electrochemical performance of the composite material. However, traditional composite technologies, such as tin-hard carbon composites prepared by mechanical ball milling, often find it difficult to achieve uniform distribution of high-specific capacity tin particles in the hard carbon matrix, let alone uniform distribution of tin particles between hard carbon layers and in pores. In addition, direct exposure of alloy materials to the electrolyte can easily cause the material to re-agglomerate, leading to a decrease in battery performance. At present, there are reported literatures that use sodium borohydride to reduce stannous chloride in aqueous solution, but because sodium borohydride reacts with water to produce hydrogen, even increasing the alkalinity of the aqueous solution cannot completely eliminate it, which is obviously not conducive to industrial production. First, the hydrogen produced by the reaction will increase the risk of fire or even explosion, which obviously violates the principle of safe production; in addition, industrial equipment is often made of steel, and the generation of hydrogen will cause hydrogen embrittlement of steel, resulting in a decrease in the mechanical strength of the equipment, accelerated aging of the instrument, and increased production costs. The method of the present invention adopts a co-solvent of water and ethanol as a reaction system, which can suppress the generation of hydrogen, and is very beneficial to the safety and sustainability of production. In terms of the morphology of the product, the reaction system in the literature is not wetted by graphite and water, resulting in tin being generated only on the graphite surface, and it is difficult to reach the graphite interlayer. The present invention, by modifying the hard carbon surface, utilizes the self-polymerization and adsorption properties of dopamine hydrochloride to achieve uniform and dense in-situ polymerization on the hard carbon surface, improves the wettability of the hard carbon, and allows the tin salt solution to penetrate into the pores or interlayers of the hard carbon. After subsequent drying, the tin salt is "locked" on the surface, pores and interlayers of the hard carbon. When the reduction reaction of tin ions occurs later, nano-tin is generated on the surface, pores and interlayers of the hard carbon to obtain a uniformly dispersed tin-hard carbon composite material.

[0006] Liquid phase reactions can achieve uniform distribution of products due to the uniformity of the solution, and the surface morphology, particle size distribution, and crystal form of the products can be regulated by controlling the reaction conditions. Through chemical reduction reactions in the liquid phase, tin can be deposited between pores, between layers, and on the surface of hard carbon. In the process of preparing tin, due to the high reduction potential of tin, it is crucial to select an appropriate reducing agent. Different reducing agents can achieve the reduction of tin ions with different valence states, and can achieve synthesis at room temperature and pressure, reducing energy consumption. Traditional methods for synthesizing nano-tin are often very complicated and accompanied by the agglomeration of nano-tin. In addition, during the synthesis of tin-hard carbon composite negative electrodes, because hard carbon does not wet in aqueous solvents, the reaction only generates tin at the interface between hard carbon and solvent, and the agglomeration is more serious, making it impossible to achieve high dispersion of the composite material. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery, which has the characteristics of uniform deposition and dispersion, good adjustability of particle size and morphology, and strong process controllability.

[0008] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery, comprising the following steps: S1. Pretreatment of hard carbon material: using porous hard carbon as raw material, adding dopamine hydrochloride solution for pretreatment, mixing it thoroughly and filtering it out to obtain pretreated hard carbon; S2. In-situ polymerization on the hard carbon surface: adding the pretreated hard carbon into a sodium hydroxide solution to achieve in-situ polymerization of dopamine hydrochloride on the pretreated hard carbon surface, stirring to make the polymer layer completely cover the hard carbon surface, and then filtering out to obtain the hydrophilic hard carbon; S3. Preparation of composite particles: Add hydrophilic hard carbon to SnCl2 or SnCl4 solution and grind to make Sn 2+ or Sn 4+ Fully penetrate into the interlayers or open pores of hard carbon, continuously stir to obtain a suspension dispersion, and then spray-dry the dispersion to obtain SnCl2-hard carbon or SnCl4-hard carbon composite particles. This step can lock the tin element on the outer surface of hard carbon and in the internal pores, which is more conducive to improving the deposition efficiency and uniform distribution of the expensive tin element on the outer surface of hard carbon and in the pores in the subsequent steps; S4. Deposition of tin-hard carbon composite material: In an ice-water bath, add the composite particles into a sodium borohydride hydrogen evolution reaction inhibition solution with stirring. The Sn produced by the reaction is uniformly deposited on the outer surface and internal pores of the hard carbon to obtain a Sn-hard carbon composite suspension. After filtering, the suspension is repeatedly washed and filtered with deionized water to remove residual solvents and tin salts. Finally, the suspension is dried at 60-100°C to obtain a tin-hard carbon composite material.

[0009] Step S4 ensures the uniform distribution of the product tin on the inner and outer surfaces of the hard carbon, and can make the tin salt react completely to the greatest extent, improve the yield, and obtain a tin-hard carbon composite material after the reaction. Due to the low temperature conditions of ice water and the dilution of the water solvent with ethanol, the reaction greatly inhibits and slows down the hydrogen evolution side reaction of the active protons on the water molecules, avoids the intense hydrogen evolution side reaction that causes the powder and liquid to be ejected, and improves the utilization efficiency of sodium borohydride as a reducing agent. The specific equation is: 4Sn 2+ +BH4 - +8OH - →4Sn+MO2 - +6H2O or 2Sn 4+ +BH4 - +8OH -→2Sn+MO2 - +6H2O In the present invention, the surface of hard carbon is modified to enhance the wettability of hard carbon in solvent, so that the reaction can be carried out between the layers of hard carbon or even in the open pores, so that the tin is deeply dispersed and a tin-hard carbon composite negative electrode with excellent electrochemical performance is formed.

[0010] Specifically, in the present invention, by modifying the hard carbon surface, utilizing the self-polymerization and adsorption properties of dopamine hydrochloride under alkaline conditions, a poly dopamine hydrochloride film with high adhesion and adsorption is generated on the hard carbon surface, achieving uniform and dense in-situ polymerization, and improving the wettability of hard carbon. In the process of dopamine hydrochloride coating hard carbon, the benzene ring structure and phenol group in the dopamine hydrochloride molecule are first adsorbed on the surface of the charged functional group on the hard carbon surface by electrostatic action. Then, under alkaline conditions, dopamine hydrochloride undergoes an oxidation-reduction reaction to form a poly dopamine hydrochloride film, which is coated on the surface of hard carbon. Poly dopamine hydrochloride is a highly hydrophilic material, which is mainly attributed to the functional groups such as catechol and amino groups rich in its molecular structure. These functional groups enable poly dopamine hydrochloride to form hydrogen bonds with water molecules, thereby showing strong hydrophilicity, so that the tin salt solution can penetrate into the pores or interlayers of hard carbon, and the tin salt can be "locked" on the surface, pores and interlayers of hard carbon during subsequent spray drying. The reducing agent reduces the tin ions into tin nanoparticles, and the morphology and size of the generated nano-tin are regulated by adjusting the reaction conditions, resulting in a highly dispersed tin-hard carbon composite material. The obtained composite negative electrode achieves a high specific capacity due to the presence of tin, while the carbon provides a buffer space for tin to embed sodium, improving the conductivity of tin, thus obtaining a high-performance tin-hard carbon composite negative electrode.

[0011] Furthermore, the preparation method of the sodium borohydride hydrogen evolution reaction inhibition solution is: in an ice water bath, a water-ethanol solution of sodium hydroxide is prepared, sodium borohydride is added to the above, the mass fraction of sodium borohydride in the solution is controlled to be 0.1-1%, and stirring is performed to obtain a uniform sodium borohydride hydrogen evolution reaction inhibition solution.

[0012] Further, in step S1, the concentration of the dopamine hydrochloride solution is 1-5 mg / mL, and a polydopamine hydrophilic layer is formed on the hard carbon surface; specifically, an increase in the monomer concentration usually increases the polymerization growth rate and conversion rate, thereby increasing the molecular weight. This is because the higher the monomer concentration, the more monomer molecules are available for reaction, thereby increasing the possibility of polymerization reaction. When the monomer concentration is insufficient, it is not enough to completely cover the hard carbon surface. If the monomer concentration is too high, the thickness of the polymerization layer will increase, which may occupy the internal space of the Sn deposition.

[0013] Further, in step S2, the concentration of the sodium hydroxide solution is 0.05-0.5 mol / L. Specifically, the concentration of sodium hydroxide affects the reaction rate of dopamine polymerization. Within a certain concentration range, as the concentration of sodium hydroxide increases, the polymerization reaction rate may accelerate, and excessive polymerization reaction may lead to an excessively thick polymerization layer, which may occupy the internal space of the Sn deposition.

[0014] Further, in step 3, the mass ratio of hard carbon to tin element is 0.01-0.3; the concentration of tin salt is 0.01-1 mol / L; specifically, the concentration of tin salt will affect the subsequent processability. A lower tin salt concentration will reduce the spray drying efficiency and lead to higher energy consumption, while a higher concentration may lead to less liquid in the system and block the nozzle device of the spray drying equipment.

[0015] Further, in step S3, the sanding time is 30-60 minutes and the rotation speed is 1000-1500 r / min, so that the tin ions can fully penetrate into the interlayers or open pores of the hard carbon. Specifically, if the rotation speed is too low, the slurry flows slowly and the pipe opening is easily blocked.

[0016] Furthermore, in the sodium borohydride hydrogen evolution reaction inhibition solution, the molar ratio of sodium borohydride to tin salt is 1-3 to ensure that the tin salt is completely reduced and fully precipitated; the volume ratio of water to ethanol is 0.2-0.5. Specifically, the hydroxyl groups in water molecules are more active than those in ethanol molecules, and water molecules will form a large number of hydrogen bonds. This large-scale hydrogen bond has a certain effect of dispersing the negative charge on the oxygen atom, which is manifested as the polarity of water molecules being significantly stronger than that of ethanol. Therefore, the reaction of sodium borohydride with water is relatively violent, while the reaction with ethanol is relatively stable, so the addition of ethanol can inhibit hydrogen production.

[0017] Furthermore, in step S3, the spray drying conditions are: the air inlet temperature during spray drying is 100-200°C to ensure an effective drying process; and the air outlet temperature is 50-90°C.

[0018] Furthermore, in step S1, the mixing method is one or more of stirring, ultrasound, ball milling, and shaking.

[0019] Furthermore, in steps S1 and S2, the filtering method is one or more of centrifugation, suction filtration, and filtration.

[0020] The effect of the tin-hard carbon composite material obtained by the present invention is different from that of the traditional method, but it has better electrochemical performance as a whole. The reason for achieving better effect is: (1) The ratios of the obtained tin-hard carbon composite materials are different. The composite material with a higher carbon ratio has better conductivity, can provide a larger buffer space for tin expansion, and has better cycle stability.

[0021] (2) The concentration of tin salt affects the distribution and dispersibility of tin in carbon materials. Lower tin salt concentrations may lead to uneven distribution of tin, while higher concentrations may lead to excessive aggregation of tin. Poor tin dispersion will affect the electrochemical properties of the composite, such as capacity and cycle stability.

[0022] (3) The effect of different amounts of sodium borohydride is different. The amount of sodium borohydride plays an important role in the reduction efficiency of tin and the morphology of the complex. An appropriate amount of sodium borohydride can ensure that tin ions are fully reduced, but an excessive amount may cause side reactions or lead to excessive deposition of tin, affecting the morphology and structure of the material.

[0023] The present invention provides a method for preparing a highly dispersed sodium ion battery tin-hard carbon composite negative electrode material, which has the following beneficial effects: First, the deposition is uniform and dispersed. Since hard carbon has a porous and interlayer structure, Sn is usually unable to be deposited inside the gap in the traditional liquid phase synthesis method, which is the bottleneck of Sn deposition on hard carbon. The present invention performs surface modification on hard carbon before the reaction, and utilizes the self-polymerization and adsorption properties of dopamine hydrochloride under alkaline conditions to generate a polyhydrochloride dopamine film with high adhesion and adsorption on the surface of hard carbon, achieving uniform in-situ polymerization and improving the wettability of hard carbon. The polyhydrochloride dopamine film does not need to be dense, a thin layer is sufficient, and the thinner the better, mainly because it can evenly enhance the hydrophilicity of the outer surface of hard carbon and the inner surface of the pore size. In the process of dopamine hydrochloride coating hard carbon, the benzene ring structure and phenol group in the dopamine hydrochloride molecule are first adsorbed on the charged functional groups on the surface of hard carbon through electrostatic action. Then, under alkaline conditions, dopamine hydrochloride undergoes polymerization to form a thin layer of polyhydrochloride dopamine, which is coated on the surface of hard carbon. Polydopamine hydrochloride is a highly hydrophilic material, which is mainly attributed to the rich functional groups such as catechol and amino in its molecular structure. These functional groups enable polydopamine hydrochloride to form hydrogen bonds with water molecules, thus showing strong hydrophilicity, allowing the tin salt solution to penetrate into the pores or interlayers of hard carbon, and the subsequent spray drying can "lock" the tin salt on the surface, pores and interlayers of hard carbon. The subsequent reducing agent reduces the tin ions in situ to tin nanoparticles, obtaining a tin-hard carbon composite negative electrode material that can be deposited between hard carbon layers and in open pores.

[0024] Second, the particle size and morphology are well adjustable and can be adjusted by controlling the concentration of the reactants. The concentration of sodium borohydride can control the nucleation and growth rate of tin particles in the liquid phase. When the concentration of sodium borohydride is low, the reduction rate of tin ions is slow, resulting in the formation of a small number of crystal nuclei, followed by the formation of larger particles in the diffusion growth stage. At this time, due to the slow reaction rate, new small crystal nuclei will continue to be generated in the solution. Since the particles obtained by spray drying are hard carbon composites with tin ions enriched on the inner and outer surfaces, these crystal nuclei have enough time and sufficient supply of tin ions to grow, resulting in a larger powder particle size. On the contrary, when the concentration of sodium borohydride is high, more tin ions participate in nucleation in a short time, resulting in the instantaneous formation of a large number of crystal nuclei, which consumes the tin ions in the solution, thereby limiting the further growth of the nanoparticles and reducing the average particle size of tin. In addition, too high a temperature will change the composition of the reaction system solution, resulting in defects in the Sn deposit layer, reducing the adhesion of the Sn deposit layer, and making it easy to fall off from the carbon matrix during repeated charge and discharge; at the same time, high temperature can easily cause the Sn metal grains to grow too large, making the Sn deposit layer fragile and brittle; thus causing the impedance to increase and the performance to deteriorate. Too low a temperature will slow down the reaction rate, causing the Sn deposit layer to grow slowly or even stop, resulting in poor surface quality. In addition, low temperatures will also make the coating adhesion insufficient and prone to peeling. Therefore, it is necessary to control the temperature within a suitable range to obtain an ideal Sn deposit layer. The obtained composite negative electrode achieves a high specific capacity due to the presence of tin, and carbon provides a buffer space for tin to embed sodium, improving the conductivity of tin, thereby obtaining a high-performance tin-hard carbon composite negative electrode.

[0025] Third, the process operation is highly controllable. Compared with the reported method, sodium borohydride is used to reduce stannous chloride in aqueous solution, because sodium borohydride and water will undergo hydrolysis reaction to produce hydrogen. Even if the alkalinity of the aqueous solution is increased, the reaction cannot be completely suppressed, which is obviously not conducive to industrial production. First, the hydrogen produced by the reaction will increase the risk of fire or even explosion, which has a major safety hazard; in addition, industrial equipment is often made of metal, and the presence of hydrogen will cause hydrogen embrittlement of metal materials, resulting in a decrease in the mechanical strength of the equipment, accelerating the aging of the instrument, and causing damage to the container or pipeline. The present invention uses water and ethanol co-solvents, and the hydroxyl groups in the water molecules are more active than those in the ethanol molecules. The water molecules will form a large number of hydrogen bonds. This large-scale hydrogen bond has a certain effect of dispersing the negative charge on the oxygen atom, which is manifested as the polarity of the water molecules being significantly stronger than ethanol. Therefore, the reaction of sodium borohydride with water is more violent, while the reaction with ethanol is relatively stable, so the addition of ethanol can inhibit hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the XRD pattern of Example 1; Figure 2The charge and discharge curve of Example 2 at a current density of 100 mA / g; Figure 3 The CV test curve of Example 3 was performed at a scan rate of 0.05 mV / s and a voltage range of 0.01-1.5 V; Figure 4 The cycle performance curve of Example 4 at a current density of 1000 mA / g; Figure 5 The charge-discharge curves of Example 5 for the first three weeks of charge-discharge at a current density of 100 mA / g; Figure 6 The rate charge and discharge curves of Example 6 were conducted at current densities of 0.1C, 0.5C, 1C, 2C, 5C and 10C (1C=847 mA / g). DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0028] The present invention discloses a method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery, comprising the following steps: S1. Pretreatment of hard carbon material: using porous hard carbon as raw material, adding dopamine hydrochloride solution for pretreatment, mixing it thoroughly and filtering it out to obtain pretreated hard carbon; S2. In-situ polymerization on the hard carbon surface: adding the pretreated hard carbon into a sodium hydroxide solution to achieve in-situ polymerization of dopamine hydrochloride on the pretreated hard carbon surface, stirring to make the polymer layer completely cover the hard carbon surface, and then filtering out to obtain the hydrophilic hard carbon; S3. Preparation of composite particles: Add hydrophilic hard carbon to SnCl2 or SnCl4 solution and grind to make Sn 2+ or Sn 4+ Fully penetrate into the interlayers or open pores of hard carbon, continuously stir to obtain a suspension dispersion, and then spray dry the dispersion to obtain SnCl2-hard carbon or SnCl4-hard carbon composite particles; S4. Deposition of tin-hard carbon composite material: under ice-water bath conditions, the composite particles are added to a sodium borohydride hydrogen evolution reaction inhibition solution with stirring. The Sn produced by the reaction is uniformly deposited on the outer surface and internal pores of the hard carbon to obtain a Sn-hard carbon composite suspension. After filtering, a tin-hard carbon composite material is obtained.

[0029] Furthermore, the preparation method of the sodium borohydride hydrogen evolution reaction inhibition solution is: in an ice water bath, a water-ethanol solution of sodium hydroxide is prepared, sodium borohydride is added to the above, the mass fraction of sodium borohydride in the solution is controlled to be 0.1-1%, and stirring is performed to obtain a uniform sodium borohydride hydrogen evolution reaction inhibition solution.

[0030] Furthermore, in step S1, the concentration of the dopamine hydrochloride solution is 1-5 mg / mL.

[0031] Further, in step S2, the concentration of the sodium hydroxide solution is 0.05-0.5 mol / L.

[0032] Furthermore, in step 3, the mass ratio of hard carbon to tin element is 0.01-0.3; and the concentration of tin salt is 0.01-1 mol / L.

[0033] Further, in step S3, the sanding time is 30-60 min, and the rotation speed is 1000-1500 r / min.

[0034] Furthermore, in the sodium borohydride hydrogen evolution reaction inhibition solution, the molar ratio of sodium borohydride to tin salt is 1-3, and the volume ratio of water to ethanol is 0.2-0.5.

[0035] Furthermore, in step S3, the spray drying conditions are: the air inlet temperature during spray drying is 100-200°C, and the air outlet temperature is 50-90°C.

[0036] Furthermore, in step S1, the mixing method is one or more of stirring, ultrasound, ball milling, and shaking.

[0037] Furthermore, in steps S1 and S2, the filtering method is one or more of centrifugation, suction filtration, and filtration.

[0038] Implementation Case 1 Step 1, select 0.1319 g of porous hard carbon material, add 10 mL of 2 mg / mL dopamine hydrochloride solution, mix ultrasonically for 30 minutes, and then filter out by centrifugation to obtain pretreated hard carbon A.

[0039] Step 2: Add the pretreated hard carbon A into a 0.1 mol / L sodium hydroxide solution and stir for 2 hours to achieve in-situ polymerization of dopamine hydrochloride on the surface of the pretreated hard carbon. Stir thoroughly to allow the polymerization layer to completely cover the surface of the hard carbon, and then filter it out by suction to obtain hydrophilic hard carbon B.

[0040] Step 3: Prepare 100 mL of 0.1 M SnCl2 solution, add hydrophilic hard carbon B and sand grind (1200 r / min, 45 min) to make Sn 2+ The mixture is fully infiltrated into the interlayers or open pores of the hard carbon and stirred continuously to obtain a suspension dispersion C. The dispersion is then spray-dried at an inlet air temperature of 150°C to obtain SnCl2-hard carbon composite particles D.

[0041] Step 4, under continuous ice-water bath conditions, 3.6 g of sodium hydroxide is dissolved in 91.2 g of water-ethanol (volume ratio 1:3) to form a uniform solution E, 4.8 g of sodium borohydride is added to solution E, and stirred to obtain a uniform solution F. The solution F system can inhibit the hydrogen evolution reaction of sodium borohydride in water.

[0042] Step 5, under ice water bath conditions, slowly add composite particles D to solution F while continuously stirring, to produce a uniform deposition reaction of Sn on the outer surface and internal pores of hard carbon, to obtain a Sn-hard carbon composite suspension, and after filtering, repeatedly wash and filter with deionized water to remove residual solvent and tin salt, and finally dry at 80°C to obtain a tin-hard carbon composite material G.

[0043] Implementation Case 2: Step 1, select 0.4451 g of porous hard carbon material, add 30 mL of 5 mg / mL dopamine hydrochloride solution, ball mill and mix for 2 hours, and then filter out by filtration to obtain pretreated hard carbon A.

[0044] Step 2: Add the pretreated hard carbon A into a 0.2 mol / L sodium hydroxide solution and stir for 1 hour to achieve in-situ polymerization of dopamine hydrochloride on the surface of the pretreated hard carbon. Stir thoroughly to allow the polymerization layer to completely cover the hard carbon surface, and then filter it out by centrifugation to obtain hydrophilic hard carbon B.

[0045] Step 3: Prepare 20 mL of 0.5 M SnCl4 solution, add hydrophilic hard carbon B and sand grind (1500 r / min, 30 min) to make Sn 4+ The mixture is fully infiltrated into the interlayers or open pores of the hard carbon and stirred continuously to obtain a suspension dispersion C. The dispersion is then spray-dried at an inlet air temperature of 150°C to obtain SnCl4-hard carbon composite particles D.

[0046] Step 4, under continuous ice-water bath conditions, 3 g of sodium hydroxide is dissolved in 75.3 g of water-ethanol (volume ratio 1:4) to form a uniform solution E, 0.76 g of sodium borohydride is added to solution E, and stirred to obtain a uniform solution F. The solution F system can inhibit the hydrogen evolution reaction of sodium borohydride in water.

[0047] Step 5, under ice water bath conditions, slowly add composite particles D into solution F while continuously stirring, to produce a uniform deposition reaction of Sn on the outer surface and internal pores of hard carbon, to obtain a Sn-hard carbon composite suspension, and after filtering, repeatedly wash and filter with deionized water to remove residual solvent and tin salt, and finally dry at 60°C to obtain a tin-hard carbon composite material G.

[0048] Implementation Case 3: Step 1, select 29.68 mg of porous hard carbon material, add 3 mL of dopamine hydrochloride solution with a concentration of 3 mg / mL, shake and mix for 2 hours, and then filter out by suction to obtain pretreated hard carbon A.

[0049] Step 2: Add the pretreated hard carbon A into a 0.05 mol / L sodium hydroxide solution and stir for 3 hours to achieve in-situ polymerization of dopamine hydrochloride on the surface of the pretreated hard carbon. Stir thoroughly to allow the polymerization layer to completely cover the hard carbon surface, and then filter it out to obtain hydrophilic hard carbon B.

[0050] Step 3: Prepare 75 mL of 0.2 M SnCl4 solution, add hydrophilic hard carbon B and sand grind (1400 r / min, 45 min) to make Sn 4+ The mixture is fully infiltrated into the interlayers or open pores of the hard carbon and stirred continuously to obtain a suspension dispersion C. The dispersion is then spray-dried at an inlet air temperature of 150°C to obtain SnCl4-hard carbon composite particles D.

[0051] Step 4, under continuous ice-water bath conditions, 0.7 mg of sodium hydroxide is dissolved in 14.1 g of water-ethanol (volume ratio 1:2) to form a uniform solution E, 0.114 g of sodium borohydride is added to solution E, and stirred to obtain a uniform solution F. The solution F system can inhibit the hydrogen evolution reaction of sodium borohydride in water.

[0052] Step 5, under ice water bath conditions, slowly add composite particles D into solution F while continuously stirring, to produce a uniform deposition reaction of Sn on the outer surface and internal pores of hard carbon, to obtain a Sn-hard carbon composite suspension, and after filtering, repeatedly wash and filter with deionized water to remove residual solvent and tin salt, and finally dry at 100°C to obtain a tin-hard carbon composite material G.

[0053] Implementation Case 4 Step 1, select 101.74 mg of porous hard carbon material, add 0.8 mL of 2.5 mg / mL dopamine hydrochloride solution, mix by ultrasonic for 45 minutes, and then filter out by centrifugation to obtain pretreated hard carbon A.

[0054] Step 2: Add the pretreated hard carbon A into a 0.3 mol / L sodium hydroxide solution and stir for 1.5 hours to achieve in-situ polymerization of dopamine hydrochloride on the surface of the pretreated hard carbon. Stir thoroughly to allow the polymerization layer to completely cover the surface of the hard carbon, and then filter it out by suction to obtain hydrophilic hard carbon B.

[0055] Step 3: Prepare 67 mL of 0.3 M SnCl2 solution, add hydrophilic hard carbon B and sand grind (1300 r / min, 45 min) to make Sn 2+The mixture was fully infiltrated into the interlayers or open pores of the hard carbon and stirred continuously to obtain a suspension dispersion C. The dispersion was then spray-dried at an inlet air temperature of 160°C to obtain SnCl2-hard carbon composite particles D.

[0056] Step 4, under continuous ice-water bath conditions, 0.113 g of sodium hydroxide is dissolved in 18.8 g of water-ethanol (volume ratio 1:3.5) to form a uniform solution E, 0.19 g of sodium borohydride is added to solution E, and stirred to obtain a uniform solution F. The solution F system can inhibit the hydrogen evolution reaction of sodium borohydride in water.

[0057] Step 5, under ice water bath conditions, slowly add composite particles D into solution F while continuously stirring, to produce a uniform deposition reaction of Sn on the outer surface and internal pores of hard carbon, to obtain a Sn-hard carbon composite suspension, and after filtering, repeatedly wash and filter with deionized water to remove residual solvent and tin salt, and finally dry at 70°C to obtain a tin-hard carbon composite material G.

[0058] Implementation Case 5: Step 1, select 7.418g of porous hard carbon material, add 1000mL of dopamine hydrochloride solution with a concentration of 4 mg / mL, mix by ultrasonic ball milling for 3 hours, and then filter out by filtration to obtain pretreated hard carbon A.

[0059] Step 2: Add the pretreated hard carbon A into a 0.25 mol / L sodium hydroxide solution and stir for 2.5 hours to achieve in-situ polymerization of dopamine hydrochloride on the surface of the pretreated hard carbon. Stir thoroughly to allow the polymerization layer to completely cover the surface of the hard carbon, and then filter it out by suction to obtain hydrophilic hard carbon B.

[0060] Step 3: Prepare 25 mL of 0.4 M SnCl4 solution, add hydrophilic hard carbon B and sand grind (1500 r / min, 60 min) to make Sn 4+ The mixture is fully infiltrated into the interlayers or open pores of the hard carbon and stirred continuously to obtain a suspension dispersion C. The dispersion is then spray-dried at an inlet air temperature of 190°C to obtain SnCl4-hard carbon composite particles D.

[0061] Step 4, under continuous ice-water bath conditions, 0.273 g of sodium hydroxide is dissolved in 34.2 g of water-ethanol (volume ratio 1:3.5) to form a uniform solution E, 3.8 g of sodium borohydride is added to solution E, and stirred to obtain a uniform solution F. The solution F system can inhibit the hydrogen evolution reaction of sodium borohydride in water.

[0062] Step 5, under ice water bath conditions, slowly add composite particles D to solution F while continuously stirring, to produce a uniform deposition reaction of Sn on the outer surface and internal pores of hard carbon, to obtain a Sn-hard carbon composite suspension, and after filtering, repeatedly wash and filter with deionized water to remove residual solvent and tin salt, and finally dry at 90°C to obtain a tin-hard carbon composite material G.

[0063] Implementation Case 6 Step 1, select 0.8903 g of porous hard carbon material, add 50 mL of 1.5 mg / mL dopamine hydrochloride solution, mix by ultrasonic vibration for 1 hour, and then filter out by suction to obtain pretreated hard carbon A.

[0064] Step 2: Add the pretreated hard carbon A into a 0.1 mol / L sodium hydroxide solution and stir for 2 hours to achieve in-situ polymerization of dopamine hydrochloride on the surface of the pretreated hard carbon. Stir thoroughly to allow the polymerization layer to completely cover the surface of the hard carbon, and then filter it out by suction to obtain hydrophilic hard carbon B.

[0065] Step 3: Prepare 200 mL of 0.05 M SnCl2 solution, add hydrophilic hard carbon B and sand grind (1000 r / min, 30 min) to make Sn 2+ The mixture is fully infiltrated into the interlayers or open pores of the hard carbon and stirred continuously to obtain a suspension dispersion C. The dispersion is then spray-dried at an inlet air temperature of 150°C to obtain SnCl2-hard carbon composite particles D.

[0066] Step 4, under continuous ice-water bath conditions, 3.96 g of sodium hydroxide is dissolved in 1238 g of water-ethanol (volume ratio 1:2.5) to form a uniform solution E, 3.8 g of sodium borohydride is added to solution E, and stirred to obtain a uniform solution F. The solution F system can inhibit the hydrogen evolution reaction of sodium borohydride in water.

[0067] Step 5, under ice water bath conditions, slowly add composite particles D into solution F while continuously stirring, to produce a uniform deposition reaction of Sn on the outer surface and internal pores of hard carbon, to obtain a Sn-hard carbon composite suspension, and after filtering, repeatedly wash and filter with deionized water to remove residual solvent and tin salt, and finally dry at 60°C to obtain a tin-hard carbon composite material G.

[0068] In order to effectively evaluate the technical effect of the present invention, the tin-carbon composite, carboxymethyl cellulose CMC and conductive carbon black SuperP obtained in the above six embodiments are slurried in a ratio of 8:1:1 and coated. The obtained electrode and sodium sheet are assembled in a glove box to obtain a sodium ion half-cell, and its electrochemical performance is measured on the Xinwei.

[0069] The electrode and sodium sheet obtained in the above example were assembled into a half-cell in a glove box with a water oxygen value of less than 0.01 ppm, and the electrochemical performance test was carried out on the Xinwei. The specific items are: Example 1 was characterized by XRD to obtain an XRD pattern; Example 2 was charged and discharged at a current density of 100 mA / g to obtain a charge and discharge curve; Example 3 CV test was performed at a scan rate of 0.05 mV / s and a voltage range of 0.01-1.5 V; Example 4 was cycled at a current density of 1000 mA / g to obtain cycle performance; Example 5 was charged and discharged at a current density of 100 mA / g to obtain the first three charge and discharge curves; Example 6: Rate charge and discharge were performed at current densities of 0.1C, 0.5C, 1C, 2C, 5C and 10C (1C=847 mA / g) to obtain rate performance.

[0070] Figure 1 It can be seen that the tin-carbon composite obtained in Example 1 has an obvious diffraction peak of tin, which is consistent with the standard spectrum of tin. Figure 1 The results show that the obtained tin crystal form is very good.

[0071] Figure 2 It can be seen that the obtained tin-carbon composite negative electrode has an ultra-high charge and discharge capacity, with a first-cycle charge capacity of up to 706.3 mAh / g and a first efficiency of up to 81.3%. The powder obtained in Example 2 has four charge and discharge platforms, which are consistent with the charge and discharge platform of tin, and has a very high charge and discharge capacity, because the obtained tin particle size is small, which is conducive to the transmission of sodium ions and can achieve overall sodium deintercalation.

[0072] Figure 3 It can be seen that the obtained tin-carbon composite negative electrode has strong reaction reversibility and reaction activity, and the CV peak is obvious, which is consistent with the charge and discharge platform of tin. Moreover, with the increase of the number of cycles, the peak current only increases and does not decrease, and there is no peak shift, indicating that the reaction polarization is small.

[0073] Figure 4 The cycle diagram of the tin-carbon composite negative electrode obtained in Example 4 at 1000 mA / g is used to calculate the capacity retention rate after different numbers of cycles (capacity retention rate = capacity after a specific number of cycles / capacity of the first cycle at the same current density). Figure 4 It can be seen that Example 4 has better cycle stability in 200 cycles, and the capacity has almost no attenuation. This is because carbon provides a buffer space for the volume expansion of tin, inhibits the crushing and pulverization of tin, and thus has good cycle performance.

[0074] Figure 5It can be seen that the first three charge-discharge curves of the tin-carbon composite negative electrode obtained in Example 5 at 100mA / g show that the reversibility of the material reaction is very good, the first three circles almost overlap without obvious platform decay, and the capacity increases slowly. And the charge-discharge curve has four platforms, which is consistent with the charge-discharge platform of tin, and the charge-discharge capacity is high, because the obtained tin particle size is small, which is conducive to the transmission of sodium ions and can achieve overall sodium deintercalation. The first three charge-discharge curves are almost the same, indicating that the reversibility of the material reaction is very high, indicating that the obtained tin purity is high.

[0075] The rate performance diagram of the electrode obtained in Example 6 at 0.1C, 0.5C, 1C, 2C, 5C and 10C (1C = 847 mA / g) ( Figure 6 ) showed that the obtained tin-carbon composite anode has excellent rate performance, and still has a capacity of 332.7 mAh / g even at a high current density of 10C, which is due to the excellent conductivity of the material and fast ion diffusion.

[0076] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery, characterized in that The following steps are involved: S1. Pretreatment of hard carbon material: using porous hard carbon as raw material, adding dopamine hydrochloride solution for pretreatment, mixing it thoroughly and filtering it out to obtain pretreated hard carbon; S2. In-situ polymerization on the hard carbon surface: adding the pretreated hard carbon into a sodium hydroxide solution to achieve in-situ polymerization of dopamine hydrochloride on the pretreated hard carbon surface, stirring to make the polymer layer completely cover the hard carbon surface, and then filtering out to obtain the hydrophilic hard carbon; S3. Preparation of composite particles: Add hydrophilic hard carbon to SnCl2 or SnCl4 solution and grind to make Sn 2+ or Sn 4+ Fully penetrate into the interlayers or open pores of hard carbon, continuously stir to obtain a suspension dispersion, and then spray dry the dispersion to obtain SnCl2-hard carbon or SnCl4-hard carbon composite particles; S4. Deposition of tin-hard carbon composite material: In an ice-water bath, the composite particles are added to a sodium borohydride hydrogen evolution reaction inhibition solution with stirring. The Sn produced by the reaction is uniformly deposited on the outer surface and internal pores of the hard carbon to obtain a Sn-hard carbon composite suspension. After filtering, a tin-hard carbon composite material is obtained.

2. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: The preparation method of the sodium borohydride hydrogen evolution reaction inhibition solution is as follows: in an ice water bath condition, a water-ethanol solution of sodium hydroxide is prepared, sodium borohydride is added to the solution, the mass fraction of the sodium borohydride in the solution is controlled to be 0.1-1%, and a uniform sodium borohydride hydrogen evolution reaction inhibition solution is obtained by stirring.

3. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S1, the concentration of the dopamine hydrochloride solution is 1-5 mg / mL.

4. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S2, the concentration of the sodium hydroxide solution is 0.05-0.5 mol / L.

5. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step 3, the mass ratio of hard carbon to tin element is 0.01-0.3; the concentration of tin salt is 0.01-1 mol / L.

6. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S3, the sanding time is 30-60 min, and the rotation speed is 1000-1500 r / min.

7. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 2, characterized in that: In the sodium borohydride hydrogen evolution reaction inhibition solution, the molar ratio of sodium borohydride to tin salt is 1-3, and the volume ratio of water to ethanol is 0.2-0.

5.

8. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S3, the spray drying conditions are: the air inlet temperature is 100-200°C and the air outlet temperature is 50-90°C during spray drying.

9. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S1 , the mixing method is one or more of stirring, ultrasound, ball milling, and shaking.

10. The method for preparing a highly dispersed tin-hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: In steps S1 and S2, the filtering method is one or more of centrifugation, suction filtration, and filtration.

Citation Information

Patent Citations

  • Nanometer tin / carbon composite material and preparation method thereof

    CN108134091A

  • Preparation method of electrode material with solid spherical tin growing on carbon cloth for sodium-ion battery negative electrodes

    CN109509880A

  • Preparation method of Sn / carbon fabric composite material used as sodium ion battery negative electrode

    CN109786716A

  • Tin-carbon composite material for lithium ion battery negative electrode and preparation method

    CN112038626A

  • Preparation method of sodium battery hard carbon / Sn composite negative electrode material

    CN115602819A